Relación entre la maternidad intensiva y burnout parental en madres que trabajan - Chavez Esquivel, Alejandra Gabriela (2021)
Intensive mothering prescribes what is the “correct way to be a mother”, creating expectations that are difficult to fulfill in the different facets of women today. The search to achieve this self-oriented and socially prescribed perfectionism is one of the causes of parental burnout. The objective of this review is to identify the relationship between intensive mothering and parental burnout in mothers who work in public and private companies. For this, it has been made a research in the databases Scopus, Proquest, Springer Link Psychology and Google Academic. Papers that met the inclusion and exclusion criteria (n = 7) were selected for analysis. In general, the quality of the studies is good, however, two of the articles leave as an opportunity for improvement to use procedures with higher standards of rigor for future research. It was found that the presence of intensive maternity is directly related to a higher level of burnout and that this negatively influences self-efficacy and professional career development within the company where mothers work, evidencing the need to orient specific policies for this population.